Rekrutmen Tenaga Kerja Harian Lepas Untuk Meningkatkan Pendapatan UMKM (Studi Kasus Sektor Usaha Kecil dan Menengah di Sidoarjo) - Khusniyah; Teguh Soedarto (JURASIMA, 2023)
Abstract. The development of MSME-scale industries (Micro, Small and MediumEnterprises) is an effort to determine the achievement of the goal of increasing the welfareof people in rural areas. Human resources are a very valuable asset for everyorganization and make a major contribution to the organization because employees workand act to achieve organizational goals. The aims of this study are 1. To find out whetherthe recruitment of freelance workers can increase the income of MSME actors 2. To Knowthe constraints in recruiting casual daily workers. The method used is a literature studywith a descriptive exploratory approach. The population in this study is cracker SMEs inKrembung District, Sidoarjo. This study uses non-probability sampling, namelypurposive sampling with the provision that SMEs have freelance daily workers. It can beconcluded 1. That the recruitment of freelance workers can increase the income ofKrupuk Krembung Sidoarjo MSME actors by 10-15%, in this case Cracker MSME actorscan employ freelance workers in the production process to the product packing process2. Constraints faced by Krupuk MSME actors related to the recruitment of casual dailyworkers, namely the difficulty of finding casual daily workers, the available workers workregularly and are paid monthly. To find freelance daily workers, usually cracker MSMEactors look for workers outside the Krembung sub-district Keywords: MSMEs, Income, Recruitment.